Methodology of Strengthening Students’ Media Literacy - Olimjon Isakov (Penerbit Jurnal Indonesia, 2024)
In today’s digital age, media literacy has become an essential skill for students. The rise of social media, fake news, and information overload necessitates that students critically evaluate and understand media messages. Media literacy involves the ability to access, analyze, evaluate, create, and communicate using various forms of media. It is not merely about learning to use digital tools, but about understanding how media influences perceptions and behavior. The growing role of media in shaping political, social, and cultural realities makes it essential to adopt methodologies that strengthen students' media literacy skills. This article explores key methodologies that educators can implement to enhance media literacy in students.